Identification, ranking and clustering of electronic banking services based on customer satisfaction: case study in bank industry. (11th August 2020) - Jouzdani, Javid; Shirouyehzad, Hadi; Maaroufi, Niloufar; Javaheri, Ali
As one of the most important service-providing organisations, banks are no exceptions. Therefore, in this research, electronic banking services, provided by a branch of an Iranian bank, are identified, ranked and clustered according to customer satisfaction levels. To achieve this goal, the channels of electronic banking services are identified and the customer satisfaction level for the services is measured through a designed questionnaire. Customer satisfaction levels are measured through the Likert scale, and the sign rank test is utilised for analyses. In order to rank the services, the Friedman test is utilised. In addition, the fuzzy C-mean algorithm is utilised to cluster the services and demographic features. The results indicate the e-services with which the customers are most and least satisfied. The clustering analysis results show that some specific groups of customers are less satisfied with some specific e-services. Finally, some managerial implications and suggestions are also provided.